Numerical Simulation of an Industrial‐Scale Prototypical Steel Melt Tundish Considering Flow Control and Cleaning Strategies. Issue 2 (25th October 2019) - Neumann, Sebastian; Asad, Amjad; Schwarze, Rüdiger
Abstract : Herein, the increase in the cleanliness of steel melt is researched using an industrial‐scale prototypical tundish. State‐of‐the‐art alumina‐coated, carbon‐bonded ceramic foam hybrid filters are used, which combine different filtration strategies for the removal of nonmetallic inclusions (NMI) in steel melts. Reactive cleaning reduces a high amount of inclusions by means of flotation because of carbon monoxide bubbles. Their formation is based on a reaction between the dissolved carbon from the filter and the oxygen of the steel melt. The direct deposition of NMI at the filter surfaces is called active filtration. Numerical simulations are performed to compare the performance of flow‐controlling applications inside the tundish and different filter developments (shape and position) to increase the cleanliness of steel melt. The continuous steel melt, the dispersed NMI as well as the carbon monoxide bubbles are calculated with an Eulerian–Lagrangian approach focusing on the inclusion removal by active filtration and reactive cleaning. Abstract : State‐of‐the‐art alumina‐coated, carbon‐bonded ceramic foam hybrid filters combine different filtration strategies for the removal of nonmetallic inclusions in steel melts. Active filtration, the direct deposition of inclusions, and reactive cleaning, which reduces a high amount of inclusions by means of flotation because of carbon monoxide bubbles, are investigated with numerical simulations considering flow‐controlling applications and filter developments.